2010
DOI: 10.1253/circj.cj-09-0971
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Randomized Controlled Trials on Treatment of Pulmonary Arterial Hypertension

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp ulmonary arterial hypertension (PAH) is a chronic and severe fatal disease that can be secondary to the cardiac, pulmonary or systemic diseases or unexplained. Studies on PAH have been carried out for more than 100 years, but therapeutic measures remain limited. Current medication for PAH consists mainly of prostacyclins, endothelin receptor antagonists and phosphodiesterase type 5 (PDE-5) inhibitors. 1 Bosentan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Conventional meta-analyses are limited by estimates between two interventions compared directly with each other, precluding assessment of comparative efficacy and safety of all available interventions. [4][5][6][7] Hence, evidence regarding the best treatment, either alone or in combination, is limited, leaving such decisions to individual clinical judgment. 8,9 A network meta-analysis approach can bridge this gap and guide both clinical decision-making and future research.…”
mentioning
confidence: 99%
“…Conventional meta-analyses are limited by estimates between two interventions compared directly with each other, precluding assessment of comparative efficacy and safety of all available interventions. [4][5][6][7] Hence, evidence regarding the best treatment, either alone or in combination, is limited, leaving such decisions to individual clinical judgment. 8,9 A network meta-analysis approach can bridge this gap and guide both clinical decision-making and future research.…”
mentioning
confidence: 99%
“…The pathogenesis of PH involves endothelial dysfunction with increased production of vasoconstrictors, e.g., endothelin-1 (ET-1), and reduced production of vasodilators, e.g., prostacyclin and nitric oxide (NO) (5,14). Despite the availability of existing PH therapies that attenuate these derangements, PH morbidity and mortality remains unacceptably high (20,44), indicating an urgent need for novel therapeutic strategies. Recent studies indicate that the nuclear hormone receptor peroxisome proliferator-activated receptor ␥ (PPAR␥), may play an important role in the pathophysiology of PH.…”
mentioning
confidence: 99%
“…1 The authors concluded that "in terms of clinical worsening and functional class amelioration, insignificant differences were found among iloprost, bosentan and sildenafil, but iloprost had the highest incidence of serious adverse events among the three drugs". 1 We have concerns about the method used in reaching these conclusions.…”
Section: To the Editormentioning
confidence: 99%